2010
DOI: 10.1016/j.jas.2010.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing between calcites formed by different mechanisms using infrared spectrometry: archaeological applications

Abstract: (L. Regev).Keywords: Calcium carbonate, infrared spectroscopy, pyrotechnology, diagenesis, ash, plaster AbstractInfrared spectrometry is a well established method for the identification of minerals. Due to its simplicity and the short time required to obtain a result, it can be practiced on-site during excavation using portable infrared spectrometers. However, the identification of a mineral may not be sufficient. For example, a lime plaster floor and a crushed chalk surface have similar appearance and are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
151
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 186 publications
(176 citation statements)
references
References 22 publications
5
151
0
1
Order By: Relevance
“…This hypothesis is supported by the presence of the fossil foraminifera that would have been recrystallized after complete calcination (Goren and Goldberg 1991). We analyzed all 25 samples with good stratigraphie information using FTIR spectroscopy to compare the atomic order/disorder properties of the calcite crystals from the top layers, the binder, and aggregate material in the lower layers using the grinding curve analysis approach described by Regev et al (2010). The 3 best samples, which are shown in Figure 2, each have a thin top layer that contains calcite that is less crystalline than the calcite contained in the bottom layers.…”
Section: Plaster Structure Composition and Layer Differencesmentioning
confidence: 97%
See 2 more Smart Citations
“…This hypothesis is supported by the presence of the fossil foraminifera that would have been recrystallized after complete calcination (Goren and Goldberg 1991). We analyzed all 25 samples with good stratigraphie information using FTIR spectroscopy to compare the atomic order/disorder properties of the calcite crystals from the top layers, the binder, and aggregate material in the lower layers using the grinding curve analysis approach described by Regev et al (2010). The 3 best samples, which are shown in Figure 2, each have a thin top layer that contains calcite that is less crystalline than the calcite contained in the bottom layers.…”
Section: Plaster Structure Composition and Layer Differencesmentioning
confidence: 97%
“…In this study, we first assessed the atomic disorder of plaster samples from Yiftahel using infrared spectroscopy (Regev et al 2010;Poduska et al 2011). From these, we selected the 3 best-preserved samples, namely those with disorder signatures most similar to modern plaster.…”
Section: K Mpoduska Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…45) [85]. It has been observed that there is a correspondence between structural characteristics such as crystallinity and the m 2 /m 4 band intensities ratio as the m 4 band is more influenced by atomic disorder than m 2 band [85][86][87]. Thus, this parameter can be used for discriminating between calcites with different structural characteristics as result of being formed in different conditions.…”
Section: Quantitative Analysis and Other Analytical Strategiesmentioning
confidence: 99%
“…23,45,46 In general, FTIR peaks will broaden when there are structural differences that influence the local coordination environment in a material. This has been well explored in the case of calcium carbonates through coordinated experimental and theoretical investigations.…”
Section: An Extended Example: Crystallinity As a Screening Toolmentioning
confidence: 99%